Risk factors for urinary tract infection in geriatric hip fracture patients: a systematic review and meta-analysis - Wang, Wei; Yao, Wei; Tang, Wanyun; Li, Yuhao; Sun, Hongbo; Ding, Wenbo (Frontiers in Medicine, 2024)
Background: Urinary tract infection (UTI) is a prevalent and consequential complication in hip fracture patients, leading to significant disability and heightened healthcare expenditures. Consequently, there is a critical need for a comprehensive systematic review to identify risk factors and establish early and effective preventive measures.Methods: A comprehensive search was performed across the PubMed, Cochrane, Embase, Web of Science, and Scopus databases (up to August 31, 2023). Article screening, data extraction, and quality assessment were independently completed by two reviewers.Results: Forty-four studies were eligible for inclusion, yielding an overall incidence rate of 11% (95% CI: 8%-14%). Our pooled analysis revealed 18 significant risk factors, including being female